My year of rest and relaxation [large type] - Moshfegh, Ottessa (Random House Large Print, 2018)
Early 2000 on New York City's Upper East Side. The alienation of an unnamed young protagonist from others is nearly complete when she initiates her yearlong siesta, during which time she experiences limited personal interactions. Her parents have died; her relationships with her bulimic best friend Reva, an ex-boyfriend, and her drug-pushing psychiatrist are unwholesome. As her pill-popping intensifies, so does her isolation and determination to leave behind the world's travails. She is also beset by dangerous blackouts induced by a powerful medication. -- adapted from back cover